The potential role of n-3 fatty acids and their lipid mediators on asthmatic airway inflammation - Tian, Yuan; Sun, JingMeng; Jiao, DongMei; Zhang, WeiYu (Frontiers in Immunology, 2024)
Asthma, is a common, significant and diverse condition marked by persistent airway inflammation, with a major impact on human health worldwide. The predisposing factors for asthma are complex and widespread. The beneficial effects of omega-3 (n-3) polyunsaturated fatty acids (PUFAs) in asthma have increasingly attracted attention recently. In asthma therapy, n-3 PUFAs may reduce asthma risk by controlling on levels of inflammatory cytokines and regulating recruitment of inflammatory cells in asthma. The specialized pro-resolving mediators (SPMs) derived from n-3 PUFAs, including the E- and D-series resolvins, protectins, and maresins, were discovered in inflammatory exudates and their biosynthesis by lipoxygenase mediated pathways elucidated., SPMs alleviated T-helper (Th)1/Th17 and type 2 cytokine immune imbalance, and regulated macrophage polarization and recruitment of inflammatory cells in asthma via specific receptors such as formyl peptide receptor 2 (ALX/FPR2) and G protein-coupled receptor 32. In conclusion, the further study of n-3 PUFAs and their derived SPMs may lead to novel anti-inflammatory asthma treatments.